2011
DOI: 10.1007/s00276-011-0847-1
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relation between distal parameters of the femur and its height and width?

Abstract: The purpose of this study was to reveal the association whether the distal morphometry of femur had a relation with femur height or width. Sixty-six adult (35 right and 31 left) dry femurs from Caucasians were used in this study. Computed tomography (CT) imaging was applied to obtain measurement values of the femur. Femur height (413.29 ± 28.40 mm) and width (29.86 ± 2.72 mm) were all checked one by one to determine the correlation with the parameters obtained. Both values exposed high rates of correlation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 28 publications
4
23
3
3
Order By: Relevance
“…Farrally and Moore (1975) reported the “anteroposterior width of femoral condyles”, but they did not clarify which condyle was measured [18]. The greater depth of both femoral condyles in men than in women and the absence of side differences, which were noticed in the present study, are in accordance with most literature studies [1, 46, 17, 20, 21]. However, Gillespie et al [13] measured the medial and lateral flange height and found no difference between men and women.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Farrally and Moore (1975) reported the “anteroposterior width of femoral condyles”, but they did not clarify which condyle was measured [18]. The greater depth of both femoral condyles in men than in women and the absence of side differences, which were noticed in the present study, are in accordance with most literature studies [1, 46, 17, 20, 21]. However, Gillespie et al [13] measured the medial and lateral flange height and found no difference between men and women.…”
Section: Discussionsupporting
confidence: 77%
“…The bicondylar width is the most frequently measured anatomic parameter of the distal femur. However, there is great variability between studies regarding the definition of measuring points as well as the measurement techniques and the type of sample [1, 47, 913, 1719]. As a result, any comparison would provide unreliable conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the morphometric studies are done with measurement by radiographs, CT scans or magnetic resonance imaging techniques which are indirect methods [2,4,[10][11][12][13][14][15]. There are studies which suggest that indirect method of measurement are found inaccurate and not precise even though they are corrected by the projection method as well as by the resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies are based on difference between gender and ethnic groups. [3,4,[10][11][12][13] Most of the morphometric studies are done with measurement by radiographs, CT scans or Magnetic resonance imaging techniques [2,4,[10][11][12][13][14][15]. There are few data available in which the study is done over dry femur by direct observations [3,16,17].…”
Section: Introductionmentioning
confidence: 99%